Codon optimization regulates IgG3 and IgM expression and glycosylation in N. benthamiana - Sun, Lin; Kallolimath, Somanath; Palt, Roman; Eminger, Florian; Strasser, Richard; Steinkellner, Herta (Frontiers in Bioengineering and Biotechnology, 2023)
Plants are being increasingly recognized for the production of complex human proteins, including monoclonal antibodies (mAbs). Various methods have been applied to boost recombinant expression, with DNA codon usage being an important approach. Here, we transiently expressed three complex human mAbs in Nicotiana benthamiana, namely one IgG3 and two IgM directed against SARS-CoV-2 as codon (CO) and non-codon optimized (NCO) variants. qRT-PCR exhibited significantly increased mRNA levels of all CO variants compared to the NCO orthologues, in line with increased protein expression. Purified CO and NCO mAbs did not exhibit obvious biochemical differences, as determined by SDS-PAGE and antigen binding activities. By contrast, enhanced production selectively impacts on glycosite occupancy and N-glycan processing, with increased mannosidic structures. The results point to a careful monitoring of recombinant proteins upon enhancing expression. Especially if it comes to therapeutic application even subtle modifications might alter product efficacy or increase immunogenicity.